PENGEMBANGAN STRATEGI PEMBELAJARAN INOVATIF BERBASIS PROYEK PADA KURIKULUM MERDEKA - Pande Gede Brahmandika; I Made Sutama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Project-Based Learning (PBL) strategy is an innovative approach that is relevant to the Independent Curriculum, which aims to create meaningful learning, improve 21st-century skills, and support student character formation. This study aims to examine the relevance, implementation, and impact of PBL strategies on student learning outcomes, while exploring the potential for its development in various educational contexts. Through a descriptive qualitative method, this study analyzes the application of PBL in integrating various disciplines, the use of technology, and its application at both formal and non-formal education levels. The results of the study show that PBL makes a significant contribution to improving students' critical thinking skills, creativity, cooperation, and responsibility. In addition, this strategy has been proven to support the implementation of the Independent Curriculum by encouraging students to be active, independent, and adaptive to real-world challenges. The potential for PBL development includes the integration of digital technology, expansion to community education, and enrichment of student character through cross-disciplinary projects. The conclusion of this study emphasizes the importance of implementing PBL strategies as the main approach in creating holistic and transformative learning experiences. With the support of education policies, teacher training, and adequate facilities, PBL can be a strategic solution in building innovative and sustainable education. Keywords: project-based learning, Independent Curriculum, educational innovation.